2021
DOI: 10.1109/access.2021.3133097
|View full text |Cite
|
Sign up to set email alerts
|

Security Analysis of LNMNT-LightWeight Crypto Hash Function for IoT

Abstract: Conventional cryptographic techniques are inappropriate for resource-constrained applications in the Internet of Things (IoT) domain because of their high resources requirement. This paper introduces a new Lightweight (LWT) hash function termed Lightweight New Mersenne Number Transform (LNMNT) Hash function, suitable for many IoT applications. The proposed LWT hash function is evaluated in terms of randomness, confusion, diffusion, distribution of hash function, and different attacks. The randomness analysis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…The experimental outcomes indicated that the projected method was effective for mitigating the number of packets up to 39% and detecting malevolent packets at an accuracy up to 99.99% in comparison with the traditional methods. N. Nabeel, et.al (2021) constructed a novel Lightweight (LWT) hash function known as Lightweight New Mersenne Number Transform (LNMNT) to secure diverse Internet of Things (IoT) applications [22]. The arbitrariness, confusion, diffusion, distributed hash function, and dissimilar attacks were considered for quantifying the constructed approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The experimental outcomes indicated that the projected method was effective for mitigating the number of packets up to 39% and detecting malevolent packets at an accuracy up to 99.99% in comparison with the traditional methods. N. Nabeel, et.al (2021) constructed a novel Lightweight (LWT) hash function known as Lightweight New Mersenne Number Transform (LNMNT) to secure diverse Internet of Things (IoT) applications [22]. The arbitrariness, confusion, diffusion, distributed hash function, and dissimilar attacks were considered for quantifying the constructed approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The basic principle is to control an object or entity's inherent random nature and facilitate the realization of PUF expression. Due to strong randomness, PUF generates a set of unique keys that is applicable to IoT applications [52]. Cryptographic functions use biometric data inputs for extracting the fuzzy functions [53] utilized for encryption, authentication, and decryption.…”
Section: Background Of Puf Schemesmentioning
confidence: 99%
“…LNMNT Hash is based on the new Mersenne number transform (NMNT). The designer provided a security analysis in [81]. The designer analyzed the randomness, obfuscation, diffusion, hash value distribution, and differential attacks.…”
Section: Sponge Constructionmentioning
confidence: 99%